Decision support system in a service-oriented control architecture for industrial automation - Leitão, Paulo (2009)
Service-oriented paradigm is becoming a suitable approach to address the demand for distributed and re-configurable control systems in industrial and factory automation environments. This paper discusses a decision support system approach for the conflict resolution and exception handling in a service-oriented control architecture for industrial automation, that uses High-level Petri nets to implement the system process control. The proposed decision support system is based on two granularity levels, one related to decision mechanisms embedded in local control components and other related to upper and global intelligent entities that provide decision-making services.